Zeolitic Imidazolate Framework: Self‐Cleaning and Antibacterial Zeolitic Imidazolate Framework Coatings (Adv. Mater. Interfaces 14/2018). Issue 14 (23rd July 2018) - Miao, Weizhen; Wang, Jing; Liu, Jindun; Zhang, Yatao
Abstract : Inspired by superhydrophobic self‐cleaning lotus leaves, a facile method for constructing superhydrophobic coating was proposed. Zeolitic Imidazolate Framework‐8 nanoparticles are mixed with polyvinylidene fluoride colloid to fabricate a dual hierarchical structure, and POTS is added to reduce the surface free energy. The superhydrophobic coating with excellent antibacterial activity has a great potential in self‐cleaning and antibacterial fields. More details can be found in the article number1800167 by Weizhen Miao, Yatao Zhang and co‐workers.